Pengaruh Store Atmosphere , Harga Dan Kelengkapan Produk Terhadap Keputusan Pembelian Pelanggan Pada Budiman Swalayan Kota Padang (Studi Kasus Mahasiswa Feb Universitas Dharma Andalas) - Muni Ayu Lestari; Heru Aulia Azman (GLOBAL SCIENTS PUBLISHER, 2025)
This research analyzes the influence of store atmosphere, price and product completeness on customer purchasing decisions at Budiman supermarkets in Padang City (case study of FEB students at Dharma Andalas University) using quantitative methods. This research aims to determine the influence of store atmosphere, price and product completeness on customer purchasing decisions at Budiman Supermarkets in Padang City. This research uses data collection techniques in the form of questionnaires with a quantitative approach, where data is collected from 123 respondents who are FEB students at Dharma Andalas University. The population of this research was 1,062 FEB students at Dharma Andalas University. And sampling in this study used the rao soft size calculator software method to calculate the number of samples, so the sample in this study was 123 FEB students at Dharma Andalas University. Data collection was carried out through questionnaires distributed to 123 respondents, which were then analyzed using SPSS (Statistical Product and Service Solutions) software version 21. The research results show that: store atmosphere has a positive and significant influence on customer purchasing decisions at Budiman Swalayan Padang City, price has a positive and significant influence on customer purchasing decisions at Budiman Swalayan Padang City, and product completeness has a positive and significant influence on customer purchasing decisions at Budiman Swalayan Padang City, store atmosphere, price and product completeness simultaneously have a positive and significant influence on customer purchasing decisions at Budiman Swalayan Padang City.